Early Pleistocene (marine isotope stage 36–40) calcareous nannofossil assemblage data from the upper part of the Kiwada Formation, the Kazusa Group - Daisuke Kuwano; Koji Kameo; Yoshimi Kubota; Utsunomiya Masayuki; Kanako Mantoku; Makoto Okada (PANGAEA, 2024)
We present calcareous nannofossil abundance data obtained from the upper part of the Kiwada Formation, Kazusa Group, distributed in the central part of the Japanese Archipelago. The age model was improved by Kuwano et al. (2021), and the study interval ranged from marine isotope stage 41 to 36. Here, calcareous nannofossil abundance data and oxygen isotope values of benthic foraminifera used to establish the age model are uploaded.